Analysis of Triclosan Content in Cisadane River Water Using Gc-Ms (Gas Chromatography Mass Spectrometry) - Cahyowati, Merliani Nur; Rudiana, Nita; Pratiwi, Dina (Journal of Fundamental and Applied Pharmaceutical Science, 2024)
The Ministry of Environment and Forestry states that 75% of river water in Indonesia has been polluted by household and industrial waste. Triclosan (2,4,4-trichloro-2-hydroxydiphenyl-ether) is an antibacterial that is widely used in various health and household supply products, such as detergents, toothpaste, mouthwash, bath soap and so on. This study approach employs liquid-liquid extraction on sampels, which are subsequently subjected to SIM mode analysis untilizing the Gas Chromatography Mass Spectometry (GC-MS) method. River water samples were taken from 3 points, namely village areas, fishing and industry. The results of this study indicate that the levels of the three Cisadane river water samples are positive for Triclosan with levels less than 0.3%, namely at the fishing point 598x10-9%, industrial point 1076x10-9% and residential point 1584x10-9% with a retention time of 19, 37 minutes.